O cloreto de tributilestanho desregula o eixo hipotalâmico-hipofisário-adrenal em diferentes níveis em ratas - Merlo, Eduardo (2017)
Tributyltin chloride (TBT) is an environmental contaminant that is used as a biocide in antifouling paints. TBT has been shown to induce effects of endocrine disruption. However, studies evaluating the effects of TBT on the hypothalamic-pituitary-adrenal (HPA) axis are especially rare. The present study demonstrates that exposure to TBT is critically responsible for the inappropriate function of the mammalian HPA axis, as well as the development of abnormal morphology in the pituitary and adrenal gland. Female rats were treated with TBT and the HPA axis morphophysiology was evaluated. High CRH, low ACTH expression and high plasma corticosterone levels were detected in TBT rats. In addition, TBT increases the expression of the iNOS protein in the rat hypothalamus. Morphophysiological abnormalities, including inflammation, altered cellular redox balance, apoptosis and collagen deposition in the pituitary and adrenal glands, in addition to increased adiposity and PPARγ protein expression in the adrenal, were observed in TBT rats. Together, these data provide in vivo evidence that TBT leads to functional dissociation between CRH, ACTH and orticosterone, which could be associated with inflammation and increased iNOS expression in the hypothalamus. Thus, TBT exerts toxic effects at different levels on HPA axis function.